2023
DOI: 10.1155/2023/9565205
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Nivolumab-Induced Vogt–Koyanagi–Harada Disease-Like Uveitis in a Patient Managed without Intravenous Methylprednisolone Therapy

Abstract: Background. In recent years, immune checkpoint inhibitors (ICI) have been often used for several types of cancers. Immune-related adverse events (irAEs) are autoimmune responses caused by ICI. Among the different types of irAEs, uveitis is common in ophthalmology. Moreover, there are reports on Vogt–Koyanagi–Harada (VKH) disease-like uveitis. In most cases, VKH, as in the usual VKH, is managed with intravenous methylprednisolone therapy. Case Report. A 72-year-old man was diagnosed with gastric cancer, and he … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A study of individual case safety reports from the WHO international pharmacovigilance database found that ICIs and protein kinase inhibitors were the only drugs associated with druginduced VKH-like uveitis [68]. Our literature search yielded 24 retrospective studies, case reports, and case series analyzing VKH-like uveitis in the context of ICI therapy, totalling 41 patients [68][69][70][100][101][102][103][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. Details of the included study data are found in Appendix B (Table A4).…”
Section: Vogt-koyanagi-harada-like Uveitismentioning
confidence: 99%
“…A study of individual case safety reports from the WHO international pharmacovigilance database found that ICIs and protein kinase inhibitors were the only drugs associated with druginduced VKH-like uveitis [68]. Our literature search yielded 24 retrospective studies, case reports, and case series analyzing VKH-like uveitis in the context of ICI therapy, totalling 41 patients [68][69][70][100][101][102][103][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. Details of the included study data are found in Appendix B (Table A4).…”
Section: Vogt-koyanagi-harada-like Uveitismentioning
confidence: 99%
“…Deeper ocular inflammation and systemic disease require intravenous high-dose corticosteroids followed by a slow taper of high-dose oral steroids. Immunosuppressive medications such as azathioprine, cyclosporine, mycophenolate, and rituximab have also been used [73]. Patients should be monitored for ocular complications that can occur in VKH including cataracts, glaucoma, and choroidal atrophy [74 ▪▪ ].…”
Section: Examples Of Disruption Of Ocular Immune Privilegementioning
confidence: 99%